RESULTS OF IMPROVING THE CONSTRUCTION OF THE PLATE HEAT EXCHANGE - Mallabayev, Odiljon; Yusupova, Nadira; Sarsenbayev, Nurlan (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
The article examines modern methods of intensifying heat exchange in plate heat exchangers by changing the geometry of channels. The effectiveness of corrugated, chevron, and zigzag structures in reducing flow resistance and increasing the heat transfer coefficient has been substantiated. The peculiarities of the influence of the slope angle of the plate relief on the turbulence of the flow and the formation of stagnant zones are analyzed. Recommendations for choosing geometry are given, taking into account operating conditions in the gas processing industry.